2017
DOI: 10.1038/labinvest.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine tract-binding protein 1 mediates pyruvate kinase M2-dependent phosphorylation of signal transducer and activator of transcription 3 and oncogenesis in anaplastic large cell lymphoma

Abstract: PKM2 (pyruvate kinase M2), a critical regulator of glycolysis, is phosphorylated by numerous growth factor receptors and oncogenic tyrosine kinases including NPM-ALK which is expressed in a subset of aggressive T-cell non-Hodgkin lymphomas known as anaplastic large cell lymphoma, ALK-positive. Our previous work demonstrated that phosphorylation of Y105-PKM2 by NPM-ALK regulates a major metabolic shift to promote lymphomagenesis. In addition to its role in metabolism, recent studies have shown that PKM2 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Nuclear PKM2 has been demonstrated to phosphorylate STAT3 at Tyr705 using a phosphate group from PEP, subsequently activating transcription of MEK5 [ 20 , 73 ] and HIF-1α [ 15 ]. The interaction of polypyrimidine tract-binding protein (PTBP1) and PKM2 facilitates phosphorylation of STAT3 Tyr705 and promotes oncogenesis in lymphoma [ 74 ]. PKM2-mediated STAT3 phosphorylation promotes progression of esophagus cancer via TGF-β1-mediated EMT [ 75 ].…”
Section: Protein Kinase Function Of Pkm2mentioning
confidence: 99%
“…Nuclear PKM2 has been demonstrated to phosphorylate STAT3 at Tyr705 using a phosphate group from PEP, subsequently activating transcription of MEK5 [ 20 , 73 ] and HIF-1α [ 15 ]. The interaction of polypyrimidine tract-binding protein (PTBP1) and PKM2 facilitates phosphorylation of STAT3 Tyr705 and promotes oncogenesis in lymphoma [ 74 ]. PKM2-mediated STAT3 phosphorylation promotes progression of esophagus cancer via TGF-β1-mediated EMT [ 75 ].…”
Section: Protein Kinase Function Of Pkm2mentioning
confidence: 99%
“…The intensity of 18 F-FDG uptake in ALCL tumours may not be an indicator of treatment response and prognosis because ALK-positive ALCL was always reported to have a better prognosis than ALK-negative ALCL [1,[5][6][7]30]. Experimental results reported by McDonnell SR may explain why ALK-positive ALCL had a higher 18 F-FDG uptake [31]. Their study demonstrated that NPM-ALK induced a metabolic shift towards aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 95%
“…3.2.1 Glycolysis PTBP1 acts as an alternative splicing repressor of the PKM1, leading to the expression of the PKM2 (Shinohara et al, 2016). PTBP1 increases the transformation of PKM1 to PKM2, and the upregulation of PTBP1 is associated with the proliferation, invasion, and migration of human breast cancer, clear-cell renal cell carcinoma (ccRCC), and anaplastic large cell lymphoma (ALCL) (He et al, 2014;Hwang et al, 2017;Jiang et al, 2017). The modulation of PKM alternative splicing and the upregulation of PTBP1 in pancreatic ductal adenocarcinoma (PDAC) cells confers drug resistance, which leads to the transition to drug-resistant PDAC (DR-PDAC) (Calabretta et al, 2016).…”
Section: Processes Regulated By Ptbp1 In Cancermentioning
confidence: 99%
“…PKM2 functions as an essential gene for the Warburg effect, a cancer-specific energy metabolism state that is regulated by the alternative splicing of PTBP1 (Hwang et al, 2017;Taniguchi et al, 2018). PTBP1 is a splicer of PKM mRNA and a positive regulator of the Warburg effect.…”
Section: Conclusion and Perspectivementioning
confidence: 99%